Comment: A More Optimistic View of Cross-Border Insolvency - Jay Lawrence Westbrook (Washington University Law Quarterly, 1994)
In re Axona and In re Maxwell Communication Corp, along with other cases in other jurisdictions, demonstrate a remarkable level of cooperation in international insolvency in comparison with the discouraging results accepted as inevitable just a few years ago. When one considers these concrete results in the courts in conjunction with the rapidly expanding international initiatives for reform in this field, the prospects seem distinctly ungloomy.
Keywords: Bankruptcy; International; United States; International bankruptcy